TEA CONSUMPTION AND IRON-DEFICIENCY ANEMIA AMONG PREGNANT WOMAN IN BOGOR DISTRICT, INDONESIA - Putri Bungsu Machmud; Ratna Djuwita Hatma; Ahmad Syafiq (Media Gizi Mikro Indonesia, 2019)
Background. Anemia in pregnancy is an essential problem due to affect to not only the mother’s life but also to baby’s life. An iron deficiency causes about 75 percent of anemia during pregnancy. Objective. This study aimed to identify risk factors for iron deficiency among pregnant women and determine the possible link between iron status and tannin levels associated with tea consumption. Method. The population-based cross-sectional studies were conducted from secondary data of previous thesis-research in 2013, “Pengaruh Kadar Tanin pada Teh Celup terhadap Anemia Gizi Besi (AGB) pada Ibu Hamil di UPT Puskesmas Citeureup Kabupaten Bogor Tahun 2012”. The study population consisted of 94 randomly selected pregnant women. The inclusion criteria were pregnant women who participated in the previous study and have a complete antenatal care record. Demographic data were collected, including data on age, working status, gestational stage, time since last pregnancy, and parity. The information included nutritional variables, such as iron supplements, nutritional status, and iron intake. Also, data for tannin level grouped as low, medium, and high based on the frequency of daily tea consumption and tea-making habits. The linear model analysis was used to determine the influence of tea consumption on serum ferritin levels. Results. The results showed that time since last pregnancy (<2 years), parity (more than two children), reduced consumption of foods containing heme, and levels of tannin consumption (low, medium, or high) were predictors of iron-deficiency anemia. The results also suggested that tannin levels were inversely proportional to serum ferritin levels. Conclusion. Pregnant women who consumed tea with a low tannin level had the highest serum ferritin levels, whereas those who drank tea with medium and high tannin levels had the lowest serum ferritin levels.